Family cultural capital predicts student cognitive performance: The mediating role of student academic engagement and academic self-efficacy in a comparative cross-national context - Denis Djekourmane; Yang Zhang; Ming Li; Zewen Cai (PLoS ONE, 2025)
This study examines the relationships between family cultural capital and student cognitive performance, emphasizing the mediating effects of psychological and behavioral factors labeled student academic engagement and academic self-efficacy. Leveraging the PISA 2022 data, comprising 378,306 respondents from 33 OECD countries and 38 non-OECD countries/economies, we employed Partial Least Square-Structural Equation Modeling (PLS-SEM) analysis to test the hypothesized pathways and compare the relationships. The results revealed that family cultural capital has positive direct impacts on student cognitive performance, student academic engagement, and academic self-efficacy. Moreover, student academic engagement and academic self-efficacy are also positively associated with student cognitive performance. However, when comparing the results, all the direct effect sizes vary between OECD and non-OECD countries. Furthermore, student academic engagement and academic self-efficacy partially mediated the relationships, albeit with lower effects in OECD countries. The findings support the theory that cultural capital fosters student cognitive skills, also highlighting the crucial role that psychological and behavioral factors play in mediating these relationships and considering the differences between countries for theoretical and practical implications.